2015
DOI: 10.5796/electrochemistry.83.828
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of High Rate Performances for Ti-Doped Li<sub>3</sub>V<sub>2</sub>(PO<sub>4</sub>)<sub>3</sub> Cathode Materials

Abstract: Ti-doped lithium vanadium(III) phosphate cathode materials, Li 3−2x (V 1−x Ti x ) 2 (PO 4 ) 3 , were prepared by a solid state reaction. The Ti-doped samples exhibited that the γ-phase is stabilized at room temperature by substituting Ti for V sites at more than x = 0.10. The discharge capacity of the doped samples at a 60 C rate was found to be much higher than that for the non doped sample. This improved performance found for the doped cathodes was attributed to the increase in ionic conductivity given by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…The XRD pattern of LVP-P is very similar to that of LVP-P, and there is no characteristic peak of orthorhombic Li 2 Ti 2 (PO 4 ) 3 generally formed by Ti. 43 Fig. S2, Tables S1 and S2† show the Rietveld refinement analysis of LVP-P and LVP-T. 44 The unit cell lattice parameters of LVP-P are a = 8.609(5) Å, b = 8.594(5) Å, c = 12.039(5) Å, and V = 890.72(1) Å 3 , which are similar to those obtained in previous studies.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The XRD pattern of LVP-P is very similar to that of LVP-P, and there is no characteristic peak of orthorhombic Li 2 Ti 2 (PO 4 ) 3 generally formed by Ti. 43 Fig. S2, Tables S1 and S2† show the Rietveld refinement analysis of LVP-P and LVP-T. 44 The unit cell lattice parameters of LVP-P are a = 8.609(5) Å, b = 8.594(5) Å, c = 12.039(5) Å, and V = 890.72(1) Å 3 , which are similar to those obtained in previous studies.…”
Section: Resultssupporting
confidence: 80%
“…In the reports showing the effect of Ti atoms doped in the LVP materials, the oxidation state of Ti atoms is typically 4+ and the location is also at the sites of vanadium, as shown in our results. 37,41–43,45…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18), 19) In addition to LFP, the effectiveness of the present synthesis technique was confirmed for NVP. Thus, this polystyrene-derived carbon coating method developed here represents a promising technique to improve the electrochemical properties of NVP and/or to design new active materials.…”
mentioning
confidence: 57%
“…This result aligns with previous studies, which reported improved rate capacities of Ti 4+substituted LVP due to enhanced Li diffusion through the formation of Li vacancies. 27,31,40,41 Therefore, the higher capacity observed in Ti-LVP than LVP can be attributed to improved rate properties resulting from Ti 4+ substitution and the formation of Li vacancies.…”
Section: Cycle Characteristics In a Full Cell Of Lvp Substituted With...mentioning
confidence: 99%